Prognostic criteria of sensitivity to antibiotics of staphylococcus clinical strains - Gordiy Paliy; Oleksandr Nazarchuk; Neonila Osadchuk; Dmytro Paliy; Iryna Kovalenko (Kazimierz Wielki University, 2015)
Paliy Gordiy, Nazarchuk Oleksandr, Osadchuk Neonila, Paliy Dmytro, Kovalenko Iryna. Prognostic criteria of sensitivity to antibiotics of staphylococcus clinical strains. Journal of Education, Health and Sport. 2015;5(7):26-33. ISSN 2391-8306. DOI 10.5281/zenodo.19076 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A26-33 https://pbn.nauka.gov.pl/works/574289 http://dx.doi.org/10.5281/zenodo.19076 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 24.06.2015.   UDC: 576.851.252:577.18   PROGNOSTIC CRITERIA OF SENSITIVITY TO ANTIBIOTICS OF STAPHYLOCOCCUS CLINICAL STRAINS   Gordiy Paliy, Oleksandr Nazarchuk, Neonila Osadchuk, Dmytro Paliy, Iryna Kovalenko   Department of Microbiology, Virology and Immunology, Vinnytsya National Pirogov Memorial Medical University Ministry of Health of Ukraine   Abstract In the article, the new data of sensitivity to antibiotics in clinical strains of Staphylococci are presented. For the first time, analytic dependence of dynamic prognostic criteria of the change of sensitivity of S. aureus clinical strains, isolated from patients, was obtained by means of mathematical prediction. There were investigated prognosticated indexes of Staphylococcus strains' sensitivity to beta-lactams (oxacillin, ceftriaxone, imipenem and meropenem), vancomycin and linezolid. The dynamic of sensitivity decreasing to oxacillin, ceftriaxone, carbapenems (imipenem, meropenem), vancomycin (92,5 %) and high sensitivity to linezolid in clinical strains of S. aureus were found out. Key words: sensitivity, antibiotics, Staphylococcus, prognostic indexes.